RELATIONSHIP OF SELF-EFFICACY TO IMPROVING EMPLOYEE PERFORMANCE: A STUDY IN MEDAN CITY - Budi Alamsyah Siregar (UPMI Management, 2021)
To form a superior organization, it is necessary to place employees as the main supporting factor for success. This is because employees are the spearhead of implementing organizational activities to be able to achieve goals effectively. The work behavior of employees who are oriented towards high performance will be directly proportional to organizational goals. This article provides a discussion on aspects of the role of motivation as a mediating variable. The antecedent variables of motivation are leadership style, work environment, and self-efficacy. Meanwhile, the motivational consequence variable is employee performance. The sample of this research totaling 242 employees from 6 (six) financial companies in Medan City. Sampling method, using a purposive sampling technique. Data analysis, using path analysis with the help of Lisrel. The results showed that motivation was proven to play a mediating role in influencing employee performance t-count 8.93 ≥ 1.96.